Enhancing Legal Awareness of Bullying as a Preventive Strategy Against Child Violence: A Program Study at SDN 15 Bengkulu - Oktaviansi, Irga; Kusworo, Aldho; Fajar, Taufik Khairul; R, Rifai (Yayasan Daarul Huda Kruengmane, 2025)
Bullying is a serious issue in the education sector that negatively affects children’s mental, emotional, and academic development. Schools, which should serve as safe spaces for children’s growth, can instead become environments filled with psychological pressure due to students’ low legal awareness regarding bullying practices. The community service program at SD Negeri 15 Bengkulu City was designed to build students’ legal awareness of bullying as a preventive measure against child violence. The purpose of this activity was to provide an understanding of the concept of bullying, its impacts, and preventive strategies through interactive and applicable learning approaches. The implementation was carried out over four sessions from 11 August to 4 September 2025 involving 31 fifth-grade students. The Teaching Methodology approach was applied through five stages: interactive lectures, group discussions, role-playing, educational ice breaking, as well as evaluation and reflection. Each stage was designed to foster students’ cognitive, affective, and psychomotor understanding so they are able to identify, reject, and prevent bullying. The results show a significant increase in students’ understanding of the types of bullying, its consequences, and the preventive actions they can take. Students’ emotional responses during discussions and role-plays demonstrate greater sensitivity toward victims’ feelings, increased willingness to report bullying cases, and stronger commitment to creating a supportive classroom environment. The short-term impact of this program is enhanced student legal literacy on bullying, while the medium-term impact is reflected in the emergence of a culture of mutual respect in the classroom. In the long term, this program is expected to help establish a child-friendly school free from violent practices. The outputs generated include improved student legal literacy, a community service report, and a scientific publication that may serve as a reference for developing similar programs in other schools. Through a repetitive and participatory approach, this program demonstrates that building legal awareness of bullying requires a systematic process that integratively addresses children’s cognitive, affective, and behavioral aspects.